Market diffusion of residential PV and battery systems driven by self-consumption: A comparison of Sweden and Germany - Anna-Lena Klingler; Rasmus Luthander (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
With increasing number of installations of photovoltaic (PV) systems and lower equipment costs, the subsidies dedicated to residential PV systems are reduced in many countries. Instead of the subsidies for selling PV electricity, prospectively self-consumption is the key parameter for the profitability of PV systems. In this paper, we study the market diffusion of residential PV systems for de-tached houses in Germany and Sweden. For this, we develop a hybrid model of the adoption of PV installations driven by self-consumption. We model the profitability and investment decisions for PV systems in a first step and account for inhibiting factors by introducing an adoption rate. The adoption rate is based on empirical data from the market diffusion of heat pumps in Sweden. We also study the market diffusion of battery systems aimed to increase self-consumption. A base case with several sensitivities on long-term trends of different parameters is analysed to examine the variation of the market diffusion until 2040. The results show a large difference in the market share of PV systems in Germany and Sweden in 2040. A base case scenario results in a market share for PV systems of 65% of the German detached houses in 2040, compared to 12% in Sweden. The results show that the market share in Sweden is most sensitive to electricity price changes, whereas the German market is most sensitive to changes in the adoption rate. Since the high electricity price in Germany makes PV profitable for most of the households at an early stage, it is mainly the adoption rate that limits the market diffusion in Germany. For Sweden, where the electricity price is less than half of the German price, the profitability is the main limiting factor. This is reflected in the hybrid adoption model, where the market diffusion is dependent on both the profitability and the adoption rate. The market share for battery systems is 5% in Germany and 0% in Sweden in 2040 in the base case scenario. The results show the influences of several parameters on the market diffusion based on the different initial mar-ket conditions, which can be extended to other national markets.
urn:nbn:de:0011-n-5213044
Keywords: 330; Market diffusion; self-consumption; PV; battery; technology adoption